2019
DOI: 10.1158/1078-0432.ccr-18-3276
|View full text |Cite
|
Sign up to set email alerts
|

PDK1 Mediates NOTCH1-Mutated Head and Neck Squamous Carcinoma Vulnerability to Therapeutic PI3K/mTOR Inhibition

Abstract: Purpose: Head and neck squamous cell carcinoma (HNSCC) is driven largely by the loss of tumor suppressor genes, including NOTCH1, but lacks a biomarker-driven targeted therapy. Although the PI3K/mTOR pathway is frequently altered in HNSCC, the disease has modest clinical response rates to PI3K/mTOR inhibitors and lacks validated biomarkers of response. We tested the hypothesis that an unbiased pharmacogenomics approach to PI3K/ mTOR pathway inhibitors would identify novel, clinically relevant molecular vulnera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…NOTCH1 is involved in the regulation of the Akt/mTOR signaling pathway (46,47), which is widely acknowledged to promote cancer development (22)(23)(24)(25)(26)42). The present study revealed that shHSP27 decreased NOTCH1 expression, indicating that HSP27 might regulate chemoresistance in colon cancer cells via NOTCH1 and that NOTCH1 might regulate of HSP27 in the Akt/mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…NOTCH1 is involved in the regulation of the Akt/mTOR signaling pathway (46,47), which is widely acknowledged to promote cancer development (22)(23)(24)(25)(26)42). The present study revealed that shHSP27 decreased NOTCH1 expression, indicating that HSP27 might regulate chemoresistance in colon cancer cells via NOTCH1 and that NOTCH1 might regulate of HSP27 in the Akt/mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 49%
“…The binding of NOTCH1 to its ligands allows DNA-binding proteins to regulate the expression of NOTCH1 target genes, which are involved in the proliferation, differentiation and apoptosis of various tumor cells (22)(23)(24). Additionally, PI3K and its effectors, including Akt and mTOR, play a key role in the proliferation and survival of tumor cells (25). The NOTCH1-Akt/mTOR signaling pathway has been recognized as a potential therapeutic target for the treatment of cancer (26).…”
Section: Introductionmentioning
confidence: 99%
“…In the era of targeted therapy, a rare cancer like PSCC, could be included with other SCCs umbrella clinical trials targeting a specific common targetable alteration. The above findings, provides the potential rationale for the ongoing and future clinical trials in patients with NOTCH1 mutated HNSC using PI3K/mTOR inhibitors, to potentially include patients with PSCC along with HNSC cohorts 46 . Knowing that the aberrant expression of the essential NOTCH coactivator of the Mastermind-like (MAML) family provides an alternative mechanism to activate NOTCH signaling in human cancers.…”
Section: Discussionmentioning
confidence: 88%
“…As shown in Figure 2, the GC apoptosis rate of the siRNA-PIK3R2 group was significantly lower than siRNA-NC group ( Figure 2B, p<0.01), and the GC proliferation rate of the siRNA-PIK3R2 group was significantly higher than siRNA-NC group ( Figure 2C, p<0.01). Furthermore, several key genes of the PI3K pathway, insulin-like growth factor 1 receptor (IGF1R) [26], insulin receptor (INSR) [27], pyruvate dehydrogenase kinase 1 (PDK1) [28] and serine/threonine kinase 1 (AKT1) [29] were selected and detected to characterize biological functions of PIK3R2. We found that the mRNA expressions of IGF1R ( Figure 2D, p<0.01), INSR ( Figure 2D, p<0.01), PDK1 ( Figure 2D, p<0.01), and AKT1 ( Figure 2D, p<0.05) in siRNA-PIK3R2 group were all significantly lower than that in siRNA-NC group.…”
Section: Knockdown Pik3r2 Inhibits Gcs Apoptosis and Promotes Gcs Promentioning
confidence: 99%